Produção de sorvete dietético de leite de cabra, com característica simbiótica e avaliação de seu efeito funcional - Portela, Masu Capistrano Camurça (2015)
The aim of the present study was to develop symbiotic ice creams formulations, goat milk using inulin and/or frutooligosaccharides (FOS), and Bifidobacterium animalis subsp. lactis (Bb12), and to evaluate the effect of the added prebiotics on their technological characteristics, probiotic viability, and sensory acceptability: overrun, instrumental hardness and melting profile. The resistance of the probiotic incorporated in the ice cream matrix to in vitro simulated gastrointestinal (GIT) conditions was evaluated. Additionally, the post prandial glicemic response of the most accepted ice-cream formulation, based on the sensory acceptability scores, was evaluated among healthy (control n = 8) and diabetic individuals (experimental n = 6). Four ice-cream formulations were manufactured, denoted: SC (control ice-cream, containing polydextrose), SF (with 6% FOS, and Bb12), SI (with 6% inulin, and Bb12), and SFI (with 3% FOS, 3% inulin, and Bb12). The ice-creams were stored at -18 °C for up to 84 days. At the end of the storage period, the SI formulation had its instrumental hardness, melting profile and overrun increased compared to the SF ice-cream. All the diet ice-cream formulations obtained good acceptability scores, mainly the SI, which was the one chosen for the sensory evaluation within a diabetic group. The diabetic group average scores for the SI ice cream were higher than the ones abtained among the healthy painellists. The probiotic Bb12 in vitro survival test was developed during the period of at 15 and 84 days.The populations of the probiotic Bb12 in the SI, SF and SFI ice-cream were higher than 8.0 log UFC/g during the whole studied storage period, and the pH values of all the ice-creams was mantained around 6.0. In average, the survival rate of the probiotic Bb12 after the exposition to GIT conditions was 74%, and the prebiotics inulin and FOS contributed to Bb12 resistance. The glicemic response of the control group showed a significant difference (p<0,01) in lowering the glicemic answer compared to glucose and the post prandial levels of the experimental group were lower after the ice-cream consumption, although there was not a significant difference compared to glucose (p>0,05). The addition of 6% of inulin to the diet ice-cream (SI) showed a hipoglicemic effect, especially among the control group. The developed ice-cream formulations showed to be good vehicles to Bb12, being in conformity to the Brazilian legislation for probiotic products and maintaining high populations after the exposure to in vitro simulated GIT conditions. This work corroborates the literature data showing the prebiotic inulin and FOS as potencially texturizing ingredients, adequate to the production of simbiotic diet ice-creams with a good sensory acceptability. The new product can contributes, if offered in large scale, for the availability of diet and functional ice-cream for consumers choice.